Quasilinearization for the Boundary Value Problem of Second-Order Singular Differential System - Peiguang Wang; Tiantian Kong (Abstract and Applied Analysis)
We study the boundary value problems of second-order singular differential equations. At first, we reduce the BVPs to initial value problems of first-order singular integrodifferential equations and then we employ the quasilinearization method in studying the IVPs and obtain two monotone iterative sequences, which converge uniformly and quadratically to the unique solution of the IVPs. Finally, we get the similar result for the given BVPs.